A New Benzofuran Glycoside and Indole Alkaloids from a Sponge-Associated Rare Actinomycete, Amycolatopsis sp. - Yun Kwon; Seong-Hwan Kim; Yoonho Shin; Munhyung Bae; Byung-Yong Kim; Sang Kook Lee; Ki-Bong Oh; Jongheon Shin; Dong-Chan Oh (Marine Drugs, 2014)
Three new secondary metabolites, amycofuran (1), amycocyclopiazonic acid (2), and amycolactam (3), were isolated from the sponge-associated rare actinomycete Amycolatopsis sp. Based on combined spectroscopic analyses, the structures of 1–3 were determined to be a new benzofuran glycoside and new indole alkaloids related to cyclopiazonic acids, a class that has previously only been reported in fungi. The absolute configurations of 1 and 3 were deduced by ECD calculations, whereas that of 2 was determined using the modified Mosher method. Amycolactam (3) displayed significant cytotoxicity against the gastric cancer cell line SNU638 and the colon cancer cell line HCT116.